Evaluating the Effects of Electricity on Fish Embryos as a Potential Strategy for Controlling Invasive Cyprinids. Issue 1 (4th December 2012) - Nutile, Sam; Amberg, Jon J.; Goforth, Reuben R.
Abstract: Fish embryo responses to electricity have been evaluated to investigate impacts of electrofishing on survival of fish embryos. However, use of electricity as a lethal means of control for early life history stages of unwanted invasive fish species has not been investigated. We exposed Fathead Minnow Pimephales promelas and Zebrafish Danio rerio embryos at multiple developmental stages to voltage gradients between 2 and 24 V/cm with pulsed direct current (PDC) and virtual direct current (VDC) for 20 and 60 s. Goldfish Carassius auratus embryos were similarly exposed to the same voltage gradients, although these trials were limited to VDC for 60 s. Voltage gradients ≥20 V/cm resulted in significantly lower survival for Fathead Minnow and Zebrafish embryos, and Goldfish embryos exhibited significantly reduced survival at voltage gradients ≥16 V/cm. Zebrafish embryos also exhibited significantly lower survival with longer exposure duration and when exposed to VDC versus PDC, although Fathead Minnow embryo survival did not differ across exposure durations or current types. Based on these results, the use of electrical barriers to control bigheaded carps at early life history stages is likely impractical due to the large voltage gradients and high power densities necessary to transfer lethal power to embryos in open systems with ambient conductivities >300 μS/cm. The larger size of bigheaded carp eggs relative to those of our proxy cyprinids may make them more susceptible to lower voltage gradients. However, exploratory tests using a small number of wild‐caught bigheaded carp eggs suggested that voltage gradients and associated power densities needed to transfer lethal power to embryos under in situ ambient conductivities were similar to those required to reduce survival in the proxy fish, possibly due to the small size of the bigheaded carp embryos relative to the large void space in water‐hardened eggs.